2020
DOI: 10.1177/1753466620963030
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiectasis and increased mortality in patients with corticosteroid-dependent severe asthma: a nationwide population study

Abstract: Background: Long-term corticosteroid (CS) use is associated with increased mortality in patients with asthma, and comorbid bronchiectasis is also associated with frequent asthma exacerbation and increased healthcare use. However, there is limited information on whether bronchiectasis further increases mortality in patients with CS-dependent asthma. This study examined the impact of bronchiectasis on mortality in patients with CS-dependent asthma. Methods: A retrospective cohort of patients with CS-dependent as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
1
14
0
1
Order By: Relevance
“…Previous research revealed that patients with COPD or asthma showed more severe clinical course and worse outcome if they have comorbid bronchiectasis. 13 In line with the study, comorbid airway disease may play a major role in poorer clinical outcomes in bronchiectasis patients with COVID-19.…”
Section: To the Editorsupporting
confidence: 72%
“…Previous research revealed that patients with COPD or asthma showed more severe clinical course and worse outcome if they have comorbid bronchiectasis. 13 In line with the study, comorbid airway disease may play a major role in poorer clinical outcomes in bronchiectasis patients with COVID-19.…”
Section: To the Editorsupporting
confidence: 72%
“…Many previous studies showed corticosteroid use in asthma is associated with pulmonary TB (41), which in turn, may be related to post-TB bronchiectasis. It is also well established that bronchiectasis is a common comorbidity in subjects with severe asthma (42)(43)(44). As our study is crosssectional, we could not provide the causal inferences of those conditions.…”
Section: Discussionmentioning
confidence: 81%
“…However, the difference in mortality was not signi cant after adjusting for covariables 23 . In contrast, another study evaluated the impact of bronchiectasis on mortality in patients with severe asthma and showed that bronchiectasis was associated with all-cause mortality 24 . As the former study evaluated only in-hospital mortality, and the latter evaluated severe asthma patients, there are limited data on this issue.…”
Section: Discussionmentioning
confidence: 99%